Control biológico del insecto barrenador (Diatraea saccharalis) en el cultivo de caña de azúcar (Saccharum officinarum L.)” - Murillo Villamar, Rosa Angélica (2020)
Sugar cane is one of the most important industrial crops and cultivated, not only in Ecuador it is around the world, both in the production of sugar and other derivatives that are obtained from its stem. In addition, agricultural producers who are dedicated to the production of this item do so as an economic support for families through their national and international marketing. This document seeks to be a contribution for sugar producers to be able to eradicate the stem borer Diatraea saccharalis which is a pest that causes economic damage in the cultivation of sugar cane Saccharum officinarum L., this pest attacks the crop in its larval stage in the first stage the larva attacks the leaf blade feeding on the parenchyma of the leaf, in the second stage it feeds on the midrib of the leaf and in the third and fourth stages it penetrates the stem causing the death in the growth, the best management and the most recommended is the natural and induced biological control, making natural enemy releases more efficient. In the sugar mills they maintain programs for the breeding and release of egg and larval parasitoids to control this insect, which is reported in Ecuador and is distributed in all producing areas of the country. It is a potentially important pest due to the damage it causes to crops and industrial performance.